Long-term effects of an intergenerational program on functional capacity in older adults: Results from a seven-year follow-up of the REPRINTS study. (May 2016) - Sakurai, Ryota; Yasunaga, Masashi; Murayama, Yoh; Ohba, Hiromi; Nonaka, Kumiko; Suzuki, Hiroyuki; Sakuma, Naoko; Nishi, Mariko; Uchida, Hayato; Shinkai, Shoji; Rebok, George W.; Fujiwara, Yoshinori
Highlights: We examine the long-term effects of the intergenerational picture book reading program "REPRINTS". PREPRINTS and controls are followed for seven years. REPRINTS shows positive effects on intellectual activity and social network. REPRINTS group maintained greater physical functioning compared to controls. REPRINTS may contribute to maintaining/improved functional capacity. Abstract: Background: Social engagement activities can help older adults maintain mental and physical functioning levels. This study examined the long-term effects of the intergenerational picture-book reading program "REPRINTS" (Re search ofPr oductivity byInt ergenerationalS ympathy) on older adults. Methods: After baseline assessment, participants were allowed to decide which condition they wanted to participate in: the REPRINTS intervention or control group involving only assessments. REPRINTS participants participated in group activities that involved playing a hand game and reading picture books to children at kindergartens, elementary schools, and public childcare centers, once every one–two weeks. A follow-up assessment, which focused on functional capacity (i.e., instrumental activities of daily living, intellectual activity, and social function), was conducted after seven years. The analysis included responses from 62 REPRINTS (mean age [SD] = 66.2 [5.7]) and 100 control-group participants (mean age [SD] = 68.0 [4.7]). Results: A logistic regression analysis examining intervention effects revealed that control-group participants were more likely to reduce intellectual activity and interactions with children compared to REPRINTS participants ( p  = .013 and .003, respectively). Furthermore, the REPRINTS group maintained greater functional reach compared to the control group ( p  < .001). However, the REPRINTS group was likely to stay indoors more often, compared to the control group ( p  = .045). Conclusion: The present study indicates that the REPRINTS intergenerational program has long-term, positive effects that help maintain and promote intellectual activity, physical functioning, and intergenerational exchange, although the effect of the increasing amount of physical activity is unclear.